Development of Physics Learning Devices in High School Based on Science Technology Engineering and Mathematics (STEM) Assisted by Android in Dynamic Electricity Subject Matter - Ansar, Mohammat Ari; Werdhiana, I Komang; Darsikin, Darsikin (Jurnal Riset Pendidikan MIPA, 2020)
This research is a development research with a 4D development model. The study was conducted in class XII IPA 1 and IPA 2 in SMA Negeri 1 Moutong, each class consisted of 25 students. The instruments used were observation sheets, test questions and documentation. The data obtained consisted of experimental class data and control class data. For Cognitive tests in the experimental class, data were obtained that the percentage of graduation was 89%, while for the control class the percentage of graduation was 76%. For the attitude assessment, in the experimental class the total percentage of all meetings was 84,4%, while in the control class the total percentage of all meetings was 79%. For the Skills assessment, in the experimental class the total percentage of all meetings was 80%, while in the control class the total percentage of all meetings was 76%. For Percentage of Activity of Students, in the experimental class the total percentage of all meetings was 81,3%, while in the control class the total percentage of all meetings was 79,1%. Then from the process of analyzing Validity, Reliability, Difficulty Index, and Differences in the items it was found that, 24 items were received from a total of 25 items submitted. As well as in the interview results were found, namely a positive response from the teacher and students interviewed. The performance of the Android application is very good, able to calculate each score of the experimental class students in 0 (zero) seconds. So, it was concluded that the learning devices developed and assisted with Android were valid, practical and effective quality.